Decentralising drug-resistant tuberculosis centre services by offering virtual consultancy- a Kozhikode model - George, Sunny; T. P., Rajagopal; P. C., Annamma; P. T., James; Chetambath, Ravindran (International Journal of Research in Medical Sciences, 2017)
Background: Programmatic management of Drug Resistant Tuberculosis (PMDT) recommends one week and one month hospitalisation for pre-treatment evaluation and initiation of second line medications to MDR and XDR patients respectively. Our experience in dealing with these patients prompted us to resort to decentralising DOTs plus services by offering a virtual consultancy to those cases which did not actually require hospitalisation. Aim of the study was to analyze the feasibility of decentralisation strategy adopted in DOTs plus patients to recommend it as a nationwide strategy. Methods: The study was an observational analysis conducted in the Department of Pulmonary Medicine in 373 MDR-TB patients enrolled under DOTs Plus programme for CAT-IV regime during the period between February 2009 and April 2013 and analysed the strategy of decentralization using the internet and expertise of Medical officers at the periphery. Results: The percentage utilisation of virtual consultancy was 83.7% which emphasises the fact that this is a feasible operational modification. Adverse events reported to this DRTB centre were 29.2% in the pre-proposed model period which is comparable to the model group (30.2%). Conclusions: This study shows that in a properly functioning DRTB centre decentralising the services to its peripheral centres is a feasible option utilising the virtual consultancy model as proposed.